Influence of Traumatic Events on Adolescents’ Self-Esteem: A Case Study of Kangui Village in Murang’a County, Kenya - Njuguna, Stephen David; Kivanguli, Gregory; Rakahu, Damaris (International Journal of Professional Practice, 2026)
Adolescence is often a time of development, the discovery of one’s true self, the determination of personal values, and the determination of social and vocational direction in life. However, in Kenya, adolescents have shown antisocial behavior. This has been linked to low self-esteem. The focus of this research was to establish the influence of traumatic events on adolescents’ self-esteem in Kangui Village, Murang’a County, Kenya. A descriptive research design was used in the study. The study population consisted of 229 adolescents living in Kangui Village, Murang’a County, at the time of the study. The population was small; hence, census sampling was used. Data for the study were collected using self-administered questionnaires. Self-esteem was measured using the Rosenberg Self-Esteem Scale. The reliability of the research instrument was established using Cronbach’s Alpha. All items in the questionnaire had coefficients greater than 0.7. The data were analyzed using descriptive statistics, Pearson correlation analysis, and regression analysis. It was established that the association between traumatic events and self-esteem was negative and statistically significant, as implied by r=-0.403, p-value 0.000. The regression results showed that traumatic events had a negative and statistically significant effect on self-esteem.